Microneedles: materials, fabrication, and biomedical applications. - Luo, Xiaojin; Yang, Li; Cui, Yue (Biomedical Microdevices, 2023)
The microneedles have attracted great interests for a wide range of transdermal biomedical applications, such as biosensing and drug delivery, due to the advantages of being painless, semi-invasive, and sustainable. The ongoing challenges are the materials and fabrication methods of the microneedles in order to obtain a specific shape, configuration and function of the microneedles to achieve a target biomedical application. Here, this review would introduce the types of materials of the microneedles firstly. The hardness, Young's modulus, geometric structure, processability, biocompatibility and degradability of the microneedles are explored as well. Then, the fabrication methods for the solid and hollow microneedles in recent years are reviewed in detail, and the advantages and disadvantages of each process are analyzed and compared. Finally, the biomedical applications of the microneedles are reviewed, including biosensing, drug delivery, body fluid extraction, and nerve stimulation. It is expected that this work provides the fundamental knowledge for developing new microneedle devices, as well as the applications in a variety of biomedical fields.